STRENGTHENING BUSINESS MANAGEMENT AND PRODUCTION GOVERNANCE IN LIVESTOCK FARMER GROUPS BASED ON LOCAL POTENTIAL - Haryadi; Emalia Ariska (Jurnal Pengabdian Bangsa, 2026)
This community service program aims to strengthen business management and production governance among livestock farmer groups based on local potential. The program was initiated due to limited managerial capacity, inefficient production planning, and suboptimal utilization of local resources in small-scale livestock enterprises. The implementation employed a participatory mentoring approach involving training, field assistance, and practical demonstrations related to production management, business planning, and simple financial management. Data were collected through observation, interviews, and documentation. The results indicate improvements in farmers’ understanding of production planning, cost efficiency, and business organization. In addition, farmer groups demonstrated increased awareness of the importance of structured management and sustainable production practices. This program contributes to strengthening livestock business resilience and supports local-based agricultural development.